INNOVATIVE STRATEGIES FOR TARGETED BREAST CANCER TREATMENT: BEYOND CONVENTIONAL THERAPIES (The Research of Medical Science Review, 2025)
Breast cancer is a worldwide health challenge, with alarming data highlighting its widespread effects. The significance of this condition is quantified by its prevalence and the difficulties it presents to healthcare systems, requiring a detailed examination of its epidemiology and effects. Contemporary breast cancer interventions, encompassing surgery, chemotherapy, radiation therapy, and targeted therapies, have markedly advanced in enhancing patient prognoses. Nonetheless, they possess limitations, frequently resulting in detrimental consequences and the emergence of drug resistance. This thorough overview examines the intricate topography of breast cancer, encompassing its occurrence, contemporary treatment methods, and the intrinsic limitations of current therapeutic strategies. It elucidates the potential of nanotechnology, including both inorganic and organic nanoparticles, to selectively transport therapeutic medicines to tumour locations in the fight against breast cancer. The study examines developing medicines, their related obstacles, and the future potential of targeted drug delivery in breast cancer treatment.